Financial reporting and global capital markets: a history of the international accounting standards committee 1973-2000 - Camfferman, Kees; Zeff, Stephen (London : Oxford University Press, 2007)
Business
Keywords: Financial Reporting; Capital Markets; Financing; Auditing Standards; Stocking; Leadership; Political environment; Comparability and improvements; Raising the stakes; Financial instruments; Income Tax